Parabiosis in Mice to Study Tissue Residency of Immune Cells. Issue 5 (25th May 2022) - Wang, Haiguang; Gavil, Noah Veis; Koewler, Nathan; Masopust, David; Jameson, Stephen C.
Abstract: Different populations of immune cells rely on their distinct migration patterns for immunosurveillance, immune regulation, tissue specific differentiation, and maturation. It is often important to clarify whether cells are recirculating or tissue resident, or whether tissue‐specific cells are derived from blood‐borne precursors or a tissue‐resident population. Though migration or tissue residency of immune cells critically depends on the expression of different homing molecules (chemokine receptors, tissue retention molecules, etc.), characterization based solely on the expression of homing molecules may not faithfully reflect the migration patterns of immune cells. Therefore, a more reliable method to clarify migration patterns of immune cells is required. Parabiosis is a surgical connection of two mice resulting in a shared circulatory system, which allows reliable distinction of tissue‐resident and circulating cells. Here, we describe a set of protocols for parabiosis, including technique details, pitfalls, and suggestions for optimization and troubleshooting. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of mice for parabiosis surgery Basic Protocol 2 : Parabiosis surgery Basic Protocol 3 : Recovery and use of mice after parabiosis surgery Basic Protocol 4 : Reversal of parabiotic surgery Basic Protocol 5 : Analysis of parabionts